Genetic Risk Factors In Pulmonary Thromboemboli (Reports of Five Cases) (Annals of Medical Research, 2021)
None
Keywords: Antiphospholipid Syndrome, Protein C Deficency, Protein S Deficency, Activated C Resistance, Pulmonary Thromboemboli